Answer:
NO
Explanation:
To find the length of AB
AB = sqrt( (x2-x1)^2 + (y2-y1)^2)
= sqrt ( ( 2 - -1)^2+ ( -1 -3)^2)
= sqrt( 3^2 + (-4)^2)
= sqrt(9+16)
= sqrt(25)
= 5
To find the length of AC
AC = sqrt( (x2-x1)^2 + (y2-y1)^2)
= sqrt ( ( -4 - -1)^2+ ( -1 -3)^2)
= sqrt( ( -3)^2 + (-4)^2)
= sqrt(9+16)
= sqrt(25)
= 5
To find the length of BC
BC = sqrt( (x2-x1)^2 + (y2-y1)^2)
= sqrt ( ( -4-2)^2+ ( -1 --1)^2)
= sqrt( ( -6)^2 + (0)^2)
= sqrt(36)
= 6
This is not an equilateral triangle since BC is not equal to AB = AC